2011
DOI: 10.1002/app.35569
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of epoxy functionalized PP with unique structure and its post‐ring open reaction

Abstract: This article discusses a convenient chemical approach named in situ chlorination graft copolymerization (ISCGC) to prepare epoxy functionalized isotactic polypropylene (iPP) with a unique structure. This method was carried out in the gas-solid state, and chlorine was used as radical initiator as well as terminate agent. The effect of influence factors on the structure of the functionalized PP was investigated, and it was determined by levels of grafted GMA moieties. The results showed that PP modified with GMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…For example, in the presence of peroxides, maleic anhydride can be directly grafted onto polypropylene in reactive extrusion (at T > 180 °C). The resulting maleic anhydride-grafted PP can then be metallated in another melt-reactive extrusion step , or in solution. Conceivably, the main drawback of this approach is the multi-stage synthesis process. In addition, the radical-initiated C–H functionalization of iPP concomitantly occurs with undesirable β-scission, radical transfer, and depolymerization reactions that result in low molecular weight and broad polydispersity, thus negatively impacting the mechanical properties. , It is noteworthy that while these radical reactions are difficult to control, a few methods have been developed to mitigate deleterious side-reactions and enhance chemo-/regio-selectivity. Other examples of post-reactor functionalization include transition-metal-mediated C–H functionalization reactions. ,, …”
Section: Introductionmentioning
confidence: 99%
“…For example, in the presence of peroxides, maleic anhydride can be directly grafted onto polypropylene in reactive extrusion (at T > 180 °C). The resulting maleic anhydride-grafted PP can then be metallated in another melt-reactive extrusion step , or in solution. Conceivably, the main drawback of this approach is the multi-stage synthesis process. In addition, the radical-initiated C–H functionalization of iPP concomitantly occurs with undesirable β-scission, radical transfer, and depolymerization reactions that result in low molecular weight and broad polydispersity, thus negatively impacting the mechanical properties. , It is noteworthy that while these radical reactions are difficult to control, a few methods have been developed to mitigate deleterious side-reactions and enhance chemo-/regio-selectivity. Other examples of post-reactor functionalization include transition-metal-mediated C–H functionalization reactions. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Commercial realisation that epoxide containing polymers, such as glycidyl methacrylate (GMA), could undergo such post polymerisation modications occurred in the mid 1950's, 3 whilst academic research in this eld emerged in the 1960's. [4][5][6][7] There has been a resurgence in the interest involving epoxide polymers, from reactive surfaces and functional particles, [8][9][10][11][12][13][14][15][16][17][18][19] through to polymer chain end modications with small molecule epoxides. 20,21 In particular several research groups have used GMA as an alternative method to introduce azide groups along the polymer backbone.…”
Section: Introductionmentioning
confidence: 99%
“…These signals correspond to conjugated esters derived from GMA moieties. Furthermore, in the same spectrum, the bands at 910 and 860 cm −1 , owing to ν as C-C and νC-O of the epoxy ring, respectively, completely disappeared [16,25]. These spectral changes indicated that PEG reacted with GMA by an epoxide ring-opening mechanism.…”
Section: Resultsmentioning
confidence: 73%